Life activity of pelagic communities in the ocean tropics : based on data of the 44th Cruise of the R/V "Vityaz" - Vinogradov, M. E. (Israel Program for Scientific Translations, 1973)
Based on data of the 44th Cruise of the R/V "Vityaz" in the Pacific Ocean and Coral Sea in the effort to investigate the structure and function of the biogeocenoses of the pelagic zone of the ocean.